Aethes tesserana Denis & Schiffermuller 1775 - Budashkin, Yuriy; Richter, Ignác (Zenodo, 2021)
Aethes tesserana ([Denis & Schiffermüller], 1775) Material examined. 1♀, Croatia. Paklenica Nacional Park, 23.v.2010. 2♂, Montenegro. Tuzi, Cijevna river, 25.v.2010; 1♂, Veruša, 17.vi.2011. 2♂, North Macedonia , Gopceli, 31.v.2014; 1♂, Pepelište near Negotino, 22.iv.2019. Distribution. Europe, Russia (Kaliningrad region, Karelia, European Northwest region, Central part of the European Russia, European south taiga region, Crimea, Western Caucasus, Volga–Don region, Middle Volga, Ural, South of Western Siberia, Krasnoyarsk region, Pre-Altai region), Transcaucasia, Asia Minor, Iran?, Syria ([Denis & Schiffermüller] 1775; Razowski 1970, 2002, 2009; Kuznetzov 1978; Budashkin 2009; Sinev et al. 2019). Published as part of Budashkin, Yuriy & Richter, Ignác, 2021, New records of Cochylini moths (Lepidoptera: Tortricidae) from the Balkans, pp. 441-456 in Zootaxa 5082 (5) on page 447, DOI:10.11646/zootaxa.5082.5.3, http://zenodo.org/record/5796363